"IMPROVING THE TECHNOLOGY OF FORMATION OF METHODOLOGICAL COMPETENCE OF FUTURE PRESCHOOL TEACHERS" - Surayyo Arzikulova (Galaxy International Interdisciplinary Research Journal, 2022)
The development of modern society requires special conditions for the organization of preschool education, the rapid introduction of innovations, new technologies and methods of working with children. Today there is a demand for a creative, qualified future educator who is able to develop the skills of mobilizing their personal potential in the modern system of education and development of preschool children.